Preliminary Assessment of Dressage Asymmetry within Sitting Trot and Shoulder‐in. (June 2014) - Baxter, J; Hobbs, S; Chohan, A
Abstract : Introduction: Despite dressage popularity, little research exists in relation to the rider's posture and effect on aids given to the horse. The aim was to investigate asymmetry during sitting trot and shoulder‐in between varying rider abilities. Methods: Full body kinematics were collected at 120 Hz (XSENS MVN Biomech) for 10 novice (age 28 ± 12 years, height = 168 ± 7 cm) and 10 advanced (age 29 ± 6 years, height = 163 ± 4 cm) predominantly right handed participants, with one left handed rider in each group. Range of motion for right hip, left hip, right knee, left knee, right ankle, left ankle, ASIS vertical movement, trunk rotation were generated in Visual 3D. Results: Independent t‐tests demonstrated significant differences between groups within right and left hip external rotation when straight (P < 0.001, d = 2.52; P = 0.02, d = 1.25), shoulder‐in right (P = 0.01, d = 1.47; P = 0.02, d = 1.31), only significant in right hip within shoulder‐in left (P = 0.01, d = 1.30). Axial rotation to the right was found in all conditions, with the range significantly (P<0.05) increased between groups in straight and shoulder‐in right, as did right ASIS vertical excursion when riding straight (P = 0.01, d = 1.90), and left ASIS excursion within shoulder‐in left (P = 0.04, d = 1.03). Conclusions: Right trunk axial rotation is considered closely linked to right hand dominance, rotating the rider's trunk to the dominant rein aid. Left shoulder‐in scored higher which may be because right trunk rotation is one of the aids given to the horse when executing this dressage movement. Ethical Animal Research: Study protocols approved by the University of Central Lancashire, before commencing the study.Sources of funding: none.Competing interests: none.